Electromagnetic technology on sewage treatment - Ab. Wahid, Zularisam; Othman, Fadhil; Sohaili, Johan (Faculty of Civil Engineering, 2001)
Magnetic treatments for water and wastewater attract a special attention due to their safety, ecological purity, simplicity and low operating costs. Thus this study was carried out in order to determine the feasibility and effectiveness of applying magnetic technology for a better understanding of the sewage characteristics. The main objectives of this research are to investigate the feasibility of magnetic technology in assisting sedimentation of suspended particles and to understand the mechanism and impact of magnetic application in sewage. The effects of various parameters, magnetic field strength, flow rate, usage of pin-jet and magnetic orientations are used to investigate their effectiveness on the suspended solids removal. A series of electromagnets magnets was used as a reactor in this study and the sewage was taken from Taman Sri Pulai, Johor with estimated PE of 10,300. Experiments indicate that suspended solids removal increases as magnetic field strength and exposure time are increased and flow rate is decreased. It was found out that magnetic field increases the suspended solids removal by 41 percent to 49 percent at 670 Gauss compared to untreated raw sewage. Besides that usage of pin-jet in the magnetically treatment reactors also help to increase another 6 percent of the suspended solids removal. Study carried out also shows that magnetic field enhances the suspended solids removal by accelerating the settling of sludge (settlement time) as well as increasing the sludge density. Hence this technology is definitely beneficial in reducing the volume of sedimentation tank as well as increasing the treatment plant efficiency